PENGARUH KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2016 - Yanti, Febri; Kamaliah, Kamaliah; Mela, Nanda Fito (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to find out how the influence of Audit Committee Characteristics on Earnings Management in Banking Companies Listed in Indonesia Stock Exchange Period Year 2014-2016. The population used for this research is all banking companies in Indonesia Stock Exchange with research period 2014-2016. Based on the consideration of the criteria specified, the sample is obtained as much as 39 banking companies. This study uses secondary data in the form of financial statements. The method of analysis used in this research is regression linier analysis. Based on the results of the research, the following conclusions are obtained: 1) The Size of Audit Committee has significant effect on Earnings Management where significancy value is 0,044 less than 0,05. 2)The Number of Audit Committees’ Meetings has significant effect on Earnings Management where significancy value is 0,026 less than 0,05. 3) The Independence of Audit Committee has no significant effect on Earnings Management where significancy value is 0,841 more than 0,05. and 4) Financial Expertise has no significant effect on Earnings Management where significancy value is 0,479 more than 0,05.Keywords : Size, Number of Meetings, Independence, Financial Expertise, Earnings Management, and Audit Committee